Preparation and performance of a BTDA-modified polyurea microcapsule for encapsulating avermectin - Fu, Yabo; He, Haowei; Liu, Ran; Zhu, Lei; Xia, Yining; Qiu, Jing (Colloids and surfaces, B, Biointerfaces, 2019)
[Display omitted] •Chitosan oligomer (CO) was applied in the preparation of polyurea microcapsules.•The UV-resistance of the microcapsule was enhanced by grafting BTDA to CO.•Photodegradation of avermectin was greatly reduced when embedded in the microcapsule.•The microcapsule itself was subject to photodegradation in water. A pesticide microcapsule was prepared by encapsulating avermectin (AVM) in a polyurea microcapsule via interfacial polymerization in acetic ether/water emulsion. The polyurea microcapsule was consisted of chitosan oligomer (CO) as the membrane material and diphenyl methane-4,4′-diisocyanate (MDI) as the crosslinker. A chemical modification was carried out by grafting a UV-absorbent, 3,3′,4,4′-benzophenonetetracarboxylic dianhydride (BTDA), to CO before interfacial polymerization to enhance the UV-resistance of the microcapsule. The BTDA grafted CO (CO-BTDA) and the AVM microcapsules were characterized by a variety of instrumental techniques, including NMR, FTIR, UV–vis, GPC-LS, DLS, SEM and TEM. The in vitro release test showed that the polyurea microcapsule maintained the sustained release of AVM for a longer period (up to 120 h) in comparison with the commercial AVM formulations (within 24 h). The photodegradation test revealed that the polyurea microcapsule significantly reduced the AVM degradation and extended the half-life of AVM from 4.16 h to 9.43 h. The AVM degradation was further reduced by using the BTDA-modified polyurea microcapsule. The corresponding half-life was extended up to 17.33 h and can be mediated by changing the mass ratio of BTDA: CO during the synthesis of CO-BTDA. The use of polyurea microcapsule did not raise a concern about pesticide residue as no AVM was detected after the photodegradation test. In addition, the polyurea microcapsule itself was subject to degradation under sunlight exposure, which reduced its residue in the environment.